How much do fish aggregating devices (FADs) modify the floating object environment in the ocean?. (17th January 2013) - Dagorn, Laurent; Bez, Nicolas; Fauvel, Thomas; Walker, Emily
Abstract Natural floating objects (e.g., logs) have always been a component of the habitat of tropical tunas. However, the introduction of fish aggregating devices (FADs) modifies this environment. To assess the changes due to the deployment of FADs, we compared the spatial distribution of natural and artificial floating objects (FADs), using data from observers onboard tuna purse seine vessels in the Indian Ocean from December 2006 to December 2008. Although natural objects occur more commonly in waters south of 7°S and FADs are more common in waters north of 7°S, all types of floating objects can be found everywhere. Using different spatial scales (quadrats of size 1° × 1°, 2° × 2°, 5° × 5°, and 10° × 10°), we computed the proportion of FADs observed in quadrats without natural objects. The scale of 2° × 2° quadrats represented a threshold: distributions of the two types of objects were different at scales smaller than this threshold. The strongest change that has occurred since the introduction of FADs (besides the increased catches) has been the dramatic increase in the total number of floating objects. Since the introduction of FADs, the number of objects has at least doubled everywhere (except in the Mozambique Channel and Chagos) and in some areas (e.g., Somalia area) the multiplication factor has reached as high as 20 or 40. Our study sets the ranges of values of key parameters of the floating object environment, which are crucial in the design of future experimental studies aimed at investigating the impacts of FADs on the ecology of tunas.